The Role of Green Commitment in Mediating the Influence of Sustainable Human Resources Management and Green Technology on the Innovative Behavior of Employees of the Semarang City Cooperative and Micro Business Office - Dhea Dinata; Yuanita Rani (Proceeding of The International Conference on Business and Economics, 2026)
Climate change and global demands on sustainability put public organizations in a strategic position to support the achievement of the Sustainable Development Goals (SDGs). The Semarang City Cooperatives and Micro Enterprises Office faces challenges in increasing the competitiveness of MSMEs while ensuring environmentally friendly practices. The main problem of this study is how sustainable HR management and green technology can encourage innovative employee behavior, as well as the extent to which green commitment plays a role as a mediating variable. The purpose of this study is to analyze the direct and indirect influence of these two factors on the innovative behavior of employees. The research uses a quantitative approach with an explanatory design. Primary data was obtained through a questionnaire to 80 employees using probability sampling techniques. The instrument was measured on a Likert scale of 1–5, and the analysis was performed using multiple linear regression and a Hayes mediation test (PROCESS Macro) with bootstrapping. The results of the study show that sustainable HR management and green technology have a significant effect on employees' green commitments. Green commitments have been proven to have a positive and strong influence on innovative behavior. However, the direct influence of sustainable HR management and green technology on innovative behaviors points in a negative direction, indicating the presence of organizational adaptation factors and initial resistance to change. The mediation test confirmed that green commitment is able to channel the positive influence of both independent variables on innovative behavior, thus becoming a key factor in the transformation of sustainable work culture.